2016
DOI: 10.9734/bbj/2016/28425
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression Associated with Copper Toxicity in White Birch (Betula papyrifera) Populations from a Mining Region

Abstract: The Greater Sudbury Region (GSR) is one of the most ecologically disturbed regions of Canada. Recent studies have shown that Betula papyrifera accumulate metals in roots or leaves. The main objectives of the present study were to 1) determine the effects of copper treatment on B. papyrifera under controlled conditions and 2) assess the level of expression of genes associated with copper resistance in B. papyrifera populations from metal-contaminated and uncontaminated areas. Significant differences for damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…Our results also contrast with data from other studies that focused on B. papyrifera (a hard wood species) showing a decrease in growth and the presence of leaf chlorosis and necrosis after exposure to copper (Djeukam et al, 2016) and nickel (Theriault and Nkongolo, 2016). However, Keller et al (2003) suggests that the root system surface may have an impact in the absorption of metals such as copper and potentially lead to a difference in assimilation of metals between these species (Keller et al, 2003).…”
Section: Copper Toxicitycontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results also contrast with data from other studies that focused on B. papyrifera (a hard wood species) showing a decrease in growth and the presence of leaf chlorosis and necrosis after exposure to copper (Djeukam et al, 2016) and nickel (Theriault and Nkongolo, 2016). However, Keller et al (2003) suggests that the root system surface may have an impact in the absorption of metals such as copper and potentially lead to a difference in assimilation of metals between these species (Keller et al, 2003).…”
Section: Copper Toxicitycontrasting
confidence: 99%
“…The same effects were observed in other species such as Brassica juncea, Brassica napus (Feigl et al, 2013) and Triticum aestivum (Cook et al, 1997). Djeukam et al (2016) observed a reduction in the growth of B. papyrifera seedlings treated with copper at a concentration dose of 1312 mg/kg or more compared to a water control. In this study, growth of Q. rubra plants was not significantly affected by Cu at all the doses used (130, 656 and 1312 mg/kg) and their respective control treatments.…”
Section: Copper Toxicitysupporting
confidence: 75%
See 3 more Smart Citations